2017
DOI: 10.1177/1049909117705379
|View full text |Cite
|
Sign up to set email alerts
|

Management of Opioid-Induced Constipation in Hospice Patients

Abstract: This survey provides insight into recent practices of hospice organizations in the treatment of OIC. As more agents come to market, it is likely that management of OIC will continue to evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…41 A recent nationwide survey by Hospice and Palliative Care Organization in United States revealed that nearly 90% of the patients receiving opioid analgesics were administered agents for improving bowel function that include senna, docusate, bisacodyl, lactulose, and their combinations. 42 In the same survey, the authors have also observed that less than 25% of the hospitals use methyl naltrexone, lubiprostone, and naloxegol. Mehta et al 43 performed direct pairwise meta-analysis assessing the utility of methyl naltrexone with placebo and observed a significant improvement in RFBM.…”
Section: Discussionmentioning
confidence: 93%
“…41 A recent nationwide survey by Hospice and Palliative Care Organization in United States revealed that nearly 90% of the patients receiving opioid analgesics were administered agents for improving bowel function that include senna, docusate, bisacodyl, lactulose, and their combinations. 42 In the same survey, the authors have also observed that less than 25% of the hospitals use methyl naltrexone, lubiprostone, and naloxegol. Mehta et al 43 performed direct pairwise meta-analysis assessing the utility of methyl naltrexone with placebo and observed a significant improvement in RFBM.…”
Section: Discussionmentioning
confidence: 93%
“…Linaclotide is a peptide agonist of the guanylate cyclase-C receptor involved in the intracellular conversion of guanosine 5-triphosphate to cyclic guanosine monophosphate [54]. Linaclotide has been shown to be an effective and well-tolerated agent for the treatment of chronic constipation [55][56][57][58]. Lubiprostone is a specific activator of the type 2 chloride channels at the intestinal epithelium whose activity increases the liquidity of contents [59].…”
Section: Additional Agents and Mechanisms To Oic Controlmentioning
confidence: 99%
“…W przypadku rozpoczynania terapii AO, zaleca się wdrożenie profilaktyki przeciw zaparciom, jednak im dłużej trwa leczenie opioidami, tym coraz mniej skuteczne stają się leki przeczyszczające -stosowane długotrwale mogą powodować zjawisko przyzwyczajenia, co zmusza do zwiększania dawki dla osiągnięcia optymalnego efektu przeczyszczającego. Z punktu widzenia patomechanizmu zaparć, najskuteczniejszą metodą prewencji, jak i zmniejszenia nasilenia, jest podawanie leków, będących obwodowymi antagonistami receptorów opioidowych (PAMORA) zlokalizowanych w przewodzie pokarmowym [3,5,6,15,17].…”
Section: Indukowane Przez Analgetyki Opioidowe Zaburzenia Funkcji Przewodu Pokarmowego (Oibd) Patomechanizmunclassified
“…Dodatkowo zwiększa się wchłanianie wody ze światła jelita, co prowadzi do tworzenia suchych mas kałowych. Opisane mechanizmy mogą być zaburzane przez liczne grupy leków, a to z kolei może niekorzystnie wpływać na powiązania czynnościowe, jakie istnieją pomiędzy układem opioidergicznym a cholinergicznym[3,5,6,15,17,18]. Poznanie tych zależności pomaga w zrozumieniu, dlaczego nie da się skutecznie leczyć OIBD bez…”
unclassified